Antibacterial activity of plant extracts from Brazil against fish pathogenic bacteria Atividade antibacteriana de extratos de plantas do Brasil contra bactérias patogênicas para peixes - S.B.R. Castro (Brazilian Journal of Microbiology, 2008)
The aim of this work was to evaluate the antibacterial activity of Brazilian plants extracts against fish pathogenic bacteria. Forty six methanolic extracts were screened to identify their antibacterial properties against Streptococcus agalactiae, Flavobacterium columnare and Aeromonas hydrophila. Thirty one extracts showed antibacterial activity. O objetivo deste trabalho foi avaliar a atividade antibacteriana de extratos de plantas brasileiras contra bactérias patogênicas para peixes. A atividade antibacteriana de quarenta e seis extratos metanólicos de plantas foi avaliada contra os agentes Streptococcus agalactiae, Flavobacterium columnare e Aeromonas hydrophila. Trinta e um extratos apresentaram atividade antibacteriana.